The Mechanism of Burr Inhibition for Milling CFRP with New Type of Milling Tools - YANG Xiao-fan; HUANG Zong-ming; LI You-sheng; LI Ling-xiang; SHEN Zhi-huang (Journal of Harbin University of Science and Technology)
Concerning the machining defects such as burrs while milling Carbon Fiber-reinforced Plastics( CFＲP) with ordinary cutters，the cutting mechanism of the new-type end mills for suppressing the burrs generation in milling CFＲP was analyzed. Uncoated ordinary end mill，cross-flute router，fine-cross-nick router and diamond coated fine-cross-nick router are selected to process the CFＲP under the same cutting conditions. The comparative analysis results of the surface quality，tool wear and tool life show that the cross-flute router and fine-cross-nick router can effectively suppress the burrs occurrence of the workpiece surface. . The number of cutting edges the fine-cross-nick router involved are more than the cross-flute router，so its ability of suppressing burrs is best. And the effect of suppressing burrs of right-hand end mill is worst. The diamond coated fine-cross-nick router has the longest tool life and is most suitable for milling CFＲP.